The Ur-Portrait Stephen Hero ed il processo di creazione artistica in A Portrait of the Artist as a Young Man - NATALI, ILARIA (Premio Tesi di Dottorato, 2008)
A Portrait of the Artist as a Young Man presents a non-linear compositional progression, characterised by continual fractures, bifurcations and revisions; the genetic dossier includes pre-compositional notes and works that were never published, such as Epiphanies, A Portrait of the Artist and Stephen Hero. The genetic analysis of this long process of writing, the documentation of which covers a period of around fourteen years, reveals not only how the Portrait was conceived and composed, but also Joyce's evolution as a writer from the very first evidence of his literary activity. This new perspective on Joyce's mode of composition opens the way to a range of potential interpretations of the individual texts, as well as methodological and theoretical insights regarding genetic criticism.